Special-shaped flexible battery and special-shaped flexible battery positive and negative electrode switching process
Patent Information
- Application Number
- CN202611469452.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-21
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]本发明的主要目的是提供一种异形柔性电池及异形柔性电池正负极转接工艺,旨在解决现有异形柔性电池极耳转接工艺中柔性差、焊接缺陷多及性能不稳定的问题,实现正负极转接力学性能均衡、电化学性能达标,满足异形电池的量产制备与柔性服役需求
上述的异形柔性电池及异形柔性电池正负极转接工艺,针对正极极耳端头与正极集流体、负极极耳端头与负极集流体分别采用同材质的设计,并对应实施焊接处理与低温锡焊处理,有效避免了异种金属焊接界面因热膨胀系数差异及电化学电位差导致的微裂纹、虚焊及电化学腐蚀问题;同时,配合预处理阶段的表面处理与整平工序,显著提升了转接区域的表面洁净度与贴合平整性,使得正负极转接焊点在微观尺度上形成均匀致密的冶金结合界面,从而实现了正负极转接力学性能的均衡化,即抗拉强度、抗弯折疲劳性能趋于一致,杜绝了传统工艺中因正负极焊接强度不匹配导致的局部应力集中与柔性失效,确保电池在反复弯折服役过程中极耳转接部位的结构完整性与电连接可靠性。而且,通过第一冷却与第二冷却的分步温控,有效抑制了焊接热影响区晶粒粗化及热应力残留,显著降低了焊接缺陷发生率;再结合后处理阶段对正负极转接焊点的绝缘包覆处理,在保障转接区域电气绝缘安全的同时,进一步提升了焊点的耐环境侵蚀能力与机械防护性能。上述工艺协同作用,使得本发明的异形柔性电池在具备优异柔性和弯折耐久性的同时,电化学性能指标全面达标,且工艺流程简洁、工艺窗口宽、良率高,充分满足了异形电池的规模化量产制备需求与长期柔性服役可靠性要求。
Abstract
Description
Technical Field
[0001] This invention belongs to the field of flexible irregular lithium battery manufacturing technology, and particularly relates to an irregular flexible battery and a process for connecting the positive and negative electrodes of the irregular flexible battery. Background Technology
[0002] Irregularly shaped flexible batteries are one-dimensional ultra-fine flexible energy storage devices, including fiber-shaped batteries, cable-type batteries, linear batteries, or strip-shaped batteries. They have advantages such as extreme flexibility, lightweight, and strong adaptability to irregular shapes. They can be widely used in wearable electronics, flexible smart fabrics, micro-irregularly shaped electronic devices, and other fields. Their tab connection process directly determines the battery's flexibility, structural stability, and electrochemical performance.
[0003] Currently, the tab connection of traditional wound / stacked lithium batteries generally adopts synchronous ultrasonic welding process: positive electrode aluminum current collector is ultrasonically welded with aluminum tab (aluminum to aluminum), negative electrode copper current collector is ultrasonically welded with nickel tab (copper to nickel). This traditional process can meet the welding requirements of conventional rigid and semi-flexible batteries, with stable welding formation and low contact resistance. However, if the traditional process is directly applied to irregularly shaped flexible batteries (especially ultra-fine fiber irregularly shaped flexible batteries), there are obvious technical defects: First, in the process of negative electrode copper to nickel, the hard nickel tab will form a rigid stress concentration point, which will destroy the overall flexibility of the battery. During the bending and twisting of the battery, the connection point is prone to breakage and the weld point will fall off, which cannot meet the service requirements of flexible irregularly shaped batteries. Second, when using copper enameled wire to replace nickel tab to achieve copper to copper, copper has a high melting point and a high ultrasonic welding energy threshold. For ultra-thin copper current collectors, it is difficult to accurately control the ultrasonic welding energy, which is prone to problems such as welding through the current collector, electrode wire melting, false welding, and poor contact. The welding yield is extremely low, and the battery internal resistance fluctuates greatly and the cycle stability is poor, which makes it impossible to mass-produce and apply. Therefore, there is an urgent need for a new tab connection process that can simultaneously achieve the extreme flexibility, welding reliability, and electrical performance stability of irregularly shaped flexible batteries. Summary of the Invention
[0004] The main objective of this invention is to provide a non-circular flexible battery and a non-circular flexible battery electrode transfer process, which aims to solve the problems of poor flexibility, numerous welding defects, and unstable performance in the existing non-circular flexible battery electrode transfer process, so as to achieve balanced mechanical properties and electrochemical performance of the non-circular electrode transfer, and meet the requirements for mass production and flexible service of non-circular batteries.
[0005] To achieve the above objectives, the present invention provides a process for connecting the positive and negative electrodes of an irregularly shaped flexible battery, comprising the following steps: S1. Pretreatment: The positive current collector transition area, the negative current collector transition area, the positive electrode tab end, and the negative electrode tab end are respectively surface treated and leveled.
[0006] S2. Positive electrode connection and negative electrode connection: The positive electrode tab end is welded to the positive electrode current collector connection area to form a positive electrode connection solder joint, and then subjected to the first cooling; The negative electrode tab end and the negative electrode current collector transfer area are subjected to low-temperature soldering to form a negative electrode transfer solder joint, followed by a second cooling process.
[0007] S3. Post-processing: The positive electrode transfer solder joint and the negative electrode transfer solder joint are respectively subjected to insulation coating treatment to obtain an irregularly shaped flexible battery.
[0008] The positive electrode tab and the positive current collector are made of the same metal material.
[0009] According to an embodiment of the present invention, the positive current collector is an aluminum wire.
[0010] The positive electrode tab is made of aluminum wire.
[0011] The negative electrode current collector is a copper wire.
[0012] The negative electrode tab is made of copper wire.
[0013] According to an embodiment of the present invention, the positive electrode tab end is an enameled aluminum wire with a diameter of 0.1~0.2mm.
[0014] The negative electrode tab is made of enameled copper wire with a diameter of 0.1~0.2mm.
[0015] According to an embodiment of the present invention, the welding process includes ultrasonic welding.
[0016] The welding process is performed at a pressure of 0.2~0.6 MPa.
[0017] The welding process is performed at a frequency of 20-40 kHz.
[0018] The welding process takes 0.15 to 0.5 seconds.
[0019] The pressure holding time after welding is 0.2~0.6 s.
[0020] According to an embodiment of the present invention, the soldering temperature of the low-temperature soldering is 180~220 ℃.
[0021] The welding time for the low-temperature soldering is ≤2s.
[0022] According to an embodiment of the present invention, the surface treatment of the positive current collector transfer area and the negative current collector transfer area includes micro-polishing, as well as degreasing and / or dust removal, for removing the oxide layer and oil stains on the surface of the transfer area.
[0023] The duration of the first cooling is 10~40s.
[0024] The second cooling time is 10~40s.
[0025] According to an embodiment of the present invention, the surface treatment of both the positive electrode tab end and the negative electrode tab end is a paint stripping treatment.
[0026] The length of the paint stripping process is 1~2mm.
[0027] The overlap length between the positive electrode tab end and the positive current collector transfer area is 1~2mm.
[0028] The overlap length between the negative electrode tab end and the negative electrode current collector transfer area is 1~2mm.
[0029] According to an embodiment of the present invention, the insulating coating process uses flexible insulating adhesive.
[0030] The flexible insulating adhesive includes at least one of PP, PE, and lithium battery separator materials.
[0031] This invention provides an irregularly shaped flexible battery, which is prepared using the above-mentioned irregularly shaped flexible battery positive and negative electrode transfer process.
[0032] According to an embodiment of the present invention, the outer casing of the irregularly shaped flexible battery is an FEP tube.
[0033] The positive current collector and the negative current collector are encapsulated inside the FEP tube.
[0034] The irregularly shaped flexible battery is in a fiber state.
[0035] The diameter of the irregularly shaped flexible battery is 1.35~3mm.
[0036] The protective layer of the irregularly shaped flexible battery has a thickness of 0.15~1mm.
[0037] The beneficial effects of this invention are: The aforementioned irregularly shaped flexible battery and its positive and negative electrode transfer process employ the same material for the positive electrode tab end and the positive electrode current collector, as well as the negative electrode tab end and the negative electrode current collector. Corresponding welding and low-temperature soldering processes are implemented, effectively avoiding micro-cracks, incomplete welds, and electrochemical corrosion caused by differences in thermal expansion coefficients and electrochemical potential at the interface of dissimilar metals. Simultaneously, the surface treatment and leveling processes in the pretreatment stage significantly improve the surface cleanliness and flatness of the transfer area, resulting in a uniform and dense metallurgical bonding interface at the microscale of the positive and negative electrode transfer solder joints. This achieves a balance in the mechanical properties of the positive and negative electrode transfer, meaning that tensile strength and bending fatigue resistance tend to be consistent. This eliminates localized stress concentration and flexibility failure caused by mismatched welding strength in traditional processes, ensuring the structural integrity and electrical connection reliability of the tab transfer area during repeated bending and service. Furthermore, the stepwise temperature control of the first and second cooling processes effectively suppresses grain coarsening and residual thermal stress in the weld heat-affected zone, significantly reducing the incidence of welding defects. Combined with the post-processing insulation coating of the positive and negative electrode junctions, the electrical insulation safety of the junction area is ensured, while further enhancing the junctions' resistance to environmental corrosion and mechanical protection. The synergistic effect of these processes enables the irregularly shaped flexible battery of this invention to possess excellent flexibility and bending durability while fully meeting all electrochemical performance standards. Moreover, the process is simple, has a wide process window, and a high yield, fully satisfying the needs of large-scale mass production of irregularly shaped batteries and the reliability requirements for long-term flexible service.
[0038] The irregularly shaped flexible battery prepared using the process of this invention exhibits essentially the same pull-out force between the positive and negative electrode transition regions, resulting in excellent structural stability and significantly improved bending fatigue life. The initial coulombic efficiency after battery formation can reach over 90%, and all electrochemical indicators, such as internal resistance, cycle stability, and rate performance, meet industry standards and usage requirements. This process boasts high precision and minimal thermal damage, and is adaptable to the tab connection of micron-level ultrafine fiber batteries, filling a gap in the industry for precise connection technology of ultrafine irregularly shaped flexible batteries. Furthermore, the process route is simple, with strong process compatibility, enabling automated mass production of irregularly shaped batteries in multiple specifications and in large quantities. Detailed Implementation
[0039] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0040] Furthermore, the technical solutions of the various embodiments of the present invention can be combined with each other, but only if they are based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such combination of technical solutions does not exist and is not within the scope of protection claimed by the present invention.
[0041] To achieve the above objectives, the present invention provides a process for connecting the positive and negative electrodes of an irregularly shaped flexible battery, comprising the following steps: S1. Pretreatment: The positive current collector transition area, the negative current collector transition area, the positive electrode tab end, and the negative electrode tab end are respectively surface treated and leveled.
[0042] S2. Positive electrode connection and negative electrode connection: The positive electrode tab end is welded to the positive electrode current collector connection area to form a positive electrode connection solder joint, and then subjected to the first cooling; The negative electrode tab end and the negative electrode current collector transfer area are subjected to low-temperature soldering to form a negative electrode transfer solder joint, followed by a second cooling process.
[0043] S3. Post-processing: The positive electrode transfer solder joint and the negative electrode transfer solder joint are respectively subjected to insulation coating treatment to obtain an irregularly shaped flexible battery.
[0044] The positive electrode tab and the positive current collector are made of the same metal material.
[0045] In some embodiments, the negative electrode tab and the negative electrode current collector are made of the same metal material.
[0046] The aforementioned flexible battery positive and negative electrode transfer process employs the same material for both the positive electrode tab and the positive current collector, and the negative electrode tab and the negative current collector, respectively. Corresponding welding and low-temperature soldering processes are implemented, effectively avoiding micro-cracks, incomplete welds, and electrochemical corrosion caused by differences in thermal expansion coefficients and electrochemical potential at the dissimilar metal welding interfaces. Simultaneously, the surface treatment and leveling processes in the pretreatment stage significantly improve the surface cleanliness and flatness of the transfer area, resulting in a uniform and dense metallurgical interface at the microscale of the positive and negative electrode transfer solder joints. This achieves a balance in the mechanical properties of the positive and negative electrode transfer, meaning that tensile strength and bending fatigue resistance tend to be consistent. This eliminates localized stress concentration and flexibility failure caused by mismatched welding strength in traditional processes, ensuring the structural integrity and electrical connection reliability of the tab transfer area during repeated bending and service. Furthermore, the stepwise temperature control of the first and second cooling processes effectively suppresses grain coarsening and residual thermal stress in the weld heat-affected zone, significantly reducing the incidence of welding defects. Combined with the post-processing insulation coating of the positive and negative electrode junctions, the electrical insulation safety of the junction area is ensured, while further enhancing the junctions' resistance to environmental corrosion and mechanical protection. The synergistic effect of these processes enables the irregularly shaped flexible battery of this invention to possess excellent flexibility and bending durability while fully meeting all electrochemical performance standards. Moreover, the process is simple, has a wide process window, and a high yield, fully satisfying the needs of large-scale mass production of irregularly shaped batteries and the reliability requirements for long-term flexible service.
[0047] In some embodiments, the beneficial effects of the present invention also include: 1. In the process of switching between the positive and negative electrodes of the irregularly shaped flexible battery of the present invention, there is no hard nickel material structure. The electrode tabs are flexibly matched with the battery body and can be bent, twisted and rolled at will. There is no stress concentration or breakage and shedding, which fully meets the flexible service requirements of irregularly shaped flexible batteries (especially fibrous irregularly shaped batteries).
[0048] 2. The positive electrode of this invention adopts aluminum-aluminum ultrasonic welding, which results in a tight bond and stable contact resistance; the negative electrode adopts copper-copper low-temperature tin welding, which eliminates solder burn-through, incomplete soldering, and current collector damage, thus solving the process defects of traditional copper-to-copper ultrasonic welding and significantly improving product yield.
[0049] 3. After the positive and negative electrodes of the irregularly shaped flexible battery of the present invention are transferred, the tensile strength between the positive and negative electrodes and their corresponding tabs remains basically consistent, resulting in excellent structural stability and significantly improved bending fatigue life.
[0050] 4. The irregularly shaped flexible battery prepared using the positive and negative electrode transfer process of the present invention can achieve a coulombic efficiency of over 90% during initial formation, which is basically on par with the initial efficiency of traditional rigid lithium batteries. At the same time, the battery's internal resistance, cycle stability, rate performance and other electrical performance indicators all meet industry standards and usage requirements, and there is no performance degradation problem.
[0051] 5. The process of this invention has high precision and minimal damage, and can be adapted to the tab connection of micron-level ultra-fine fiber batteries, filling the industry gap in the precise connection process of ultra-fine irregular flexible batteries.
[0052] In some embodiments, the positive and negative electrode transfer process of the irregularly shaped flexible battery of the present invention includes a synchronous transfer process for the positive and negative electrodes of the irregularly shaped flexible battery and an asynchronous transfer process for the positive and negative electrodes of the irregularly shaped flexible battery.
[0053] In some embodiments, the positive and negative electrode transfer process of the irregularly shaped flexible battery of the present invention is an asynchronous transfer process of the positive and negative electrodes of the irregularly shaped flexible battery.
[0054] In some embodiments, the positive current collector is an aluminum wire.
[0055] The positive electrode tab is made of aluminum wire.
[0056] The negative electrode current collector is a copper wire.
[0057] The negative electrode tab is made of copper wire.
[0058] In some embodiments, the positive electrode tab end is an enameled aluminum wire with a diameter of 0.1~0.2mm.
[0059] The negative electrode tab is made of enameled copper wire with a diameter of 0.1~0.2mm.
[0060] In some embodiments, the positive electrode tab end is an enameled aluminum wire with a diameter of 0.15~0.2mm.
[0061] In some embodiments, the negative electrode tab is an enameled copper wire with a diameter of 0.15~0.2mm.
[0062] In some embodiments, the welding process includes ultrasonic welding.
[0063] The welding process is performed at a pressure of 0.2~0.6 MPa.
[0064] The welding process is performed at a frequency of 20-40 kHz.
[0065] The welding process takes 0.15 to 0.5 seconds.
[0066] The pressure holding time after welding is 0.2~0.6 s.
[0067] In some embodiments, the pressure of the welding process is 0.3~0.5 MPa.
[0068] In some embodiments, the frequency of the welding process is 25~35 kHz.
[0069] In some embodiments, the welding process lasts for 0.2 to 0.4 seconds.
[0070] In some embodiments, the pressure holding time after welding is 0.3~0.5 s.
[0071] In some embodiments, the soldering temperature of the low-temperature soldering is 180~220 ℃.
[0072] The welding time for the low-temperature soldering is ≤2s.
[0073] In some embodiments, the soldering temperature of the low-temperature soldering is 190~210 ℃.
[0074] In some embodiments, the soldering time of the low-temperature soldering is 0.5~2s.
[0075] In some embodiments, the low-temperature soldering time is 0.5~1.5s.
[0076] In some embodiments, the surface treatment of the positive current collector transition area and the negative current collector transition area includes micro-polishing, as well as degreasing and / or dust removal, for removing oxide layers and oil stains from the surface of the transition area.
[0077] The duration of the first cooling is 10~40s.
[0078] The second cooling time is 10~40s.
[0079] In some embodiments, the duration of the first cooling is 10 to 20 seconds.
[0080] In some embodiments, the duration of the second cooling is 10-20 seconds.
[0081] In some embodiments, the first cooling method is used to cool the material to room temperature.
[0082] In some embodiments, cooling to room temperature is achieved through the second cooling method.
[0083] In some embodiments, the surface treatment of both the positive electrode tab and the negative electrode tab is a paint stripping process.
[0084] The length of the paint stripping process is 1~2mm.
[0085] The overlap length between the positive electrode tab end and the positive current collector transfer area is 1~2mm.
[0086] The overlap length between the negative electrode tab end and the negative electrode current collector transfer area is 1~2mm.
[0087] In some embodiments, the length of the paint stripping process is 1.2 to 1.8 mm.
[0088] In some embodiments, the insulation coating process uses flexible insulating adhesive.
[0089] The flexible insulating adhesive includes at least one of PP, PE, and lithium battery separator materials.
[0090] In some embodiments, the insulation coating process uses PP flexible insulating adhesive.
[0091] The irregularly shaped flexible battery prepared using the process of this invention exhibits essentially the same pull-out force between the positive and negative electrode transition regions, resulting in excellent structural stability and significantly improved bending fatigue life. The initial coulombic efficiency after battery formation can reach over 90%, and all electrochemical indicators, such as internal resistance, cycle stability, and rate performance, meet industry standards and usage requirements. This process boasts high precision and minimal thermal damage, and is adaptable to the tab connection of micron-level ultrafine fiber batteries, filling a gap in the industry for precise connection technology of ultrafine irregularly shaped flexible batteries. Furthermore, the process route is simple, with strong process compatibility, enabling automated mass production of irregularly shaped batteries in multiple specifications and in large quantities.
[0092] This invention provides an irregularly shaped flexible battery, which is prepared using the above-mentioned irregularly shaped flexible battery positive and negative electrode transfer process.
[0093] In some embodiments, the outer casing of the irregularly shaped flexible battery is an FEP tube.
[0094] The positive current collector and the negative current collector are encapsulated inside the FEP tube.
[0095] The irregularly shaped flexible battery is in a fiber state.
[0096] The diameter of the irregularly shaped flexible battery is 1.35~3mm.
[0097] The protective layer of the irregularly shaped flexible battery has a thickness of 0.15~1mm.
[0098] In some embodiments, the FEP pipe has an inner diameter of 1 mm and an outer diameter of 2 mm.
[0099] In some embodiments, the diameter of the irregularly shaped flexible battery is 1.8 to 2.2 mm.
[0100] In some embodiments, the protective layer thickness of the irregularly shaped flexible battery is 0.4~0.6 mm.
[0101] To further illustrate the present invention, the following examples are provided: It should be noted that the positive electrode in the embodiments of the present invention is a conventional ultra-fine fiber-shaped flexible battery, specifically: a commercial-grade 4.4V lithium cobalt oxide fiber positive electrode with a cell diameter of 0.8mm; the positive electrode current collector is an aluminum wire; the negative electrode is a graphite fiber negative electrode with a copper wire current collector.
[0102] The positive electrode tab is a 5cm long polyurethane enameled aluminum wire with a diameter of 0.2mm; the negative electrode tab is a 5cm long polyurethane enameled copper wire with a diameter of 0.2mm; the encapsulation material is FEP tubing with an inner diameter of 1mm and an outer diameter of 2mm; the electrolyte is a commercially available conventional lithium-ion battery liquid electrolyte.
[0103] Example 1 A process for connecting the positive and negative electrodes of an irregularly shaped flexible battery includes the following steps: S1. Pretreatment: Take a 15cm long positive current collector and a 15cm long negative current collector, remove the surface oxide layer, wipe with ethanol to remove dust and oil, and dry for later use; both the positive and negative electrode tabs are enameled wires, and the transition area needs to be stripped of its enamel first. Use ultra-fine sandpaper to lightly grind the ends of the positive and negative electrode tabs respectively to remove the enamel and smooth them out, exposing the metal wire. The exposed metal wire in this part is used for the transition. The length of the enamel stripping is 1.5mm, ensuring that the exposed surface of the metal wire is clean.
[0104] S2. Positive and Negative Electrode Connection: Align the stripped positive electrode tab with the positive current collector connection area, with an overlap length of 1.5mm, and perform ultrasonic welding (specifically, aluminum-aluminum ultrasonic welding) to form the positive electrode connection solder joint. The welding pressure is 0.4MPa, the welding frequency is 30kHz, the welding time is 0.3s, and the pressure is held for 0.4s after welding. After welding, allow for a first cooling period of 10s, which is natural cooling to room temperature. The solder joint should be smooth, without deformation or incomplete welding.
[0105] After the positive electrode connection is completed and the first cooling is achieved, align the stripped negative electrode tab with the negative current collector connection area, with an overlap length of 1.5 mm. Perform a copper-to-copper low-temperature soldering process for 1 second at a soldering temperature of 200 ℃. The solder should evenly wet the bonding surface between the copper current collector and the copper enameled wire, without any solder buildup, missing solder, or current collector burn-through. Perform a second cooling process for 10 seconds, which is natural cooling to room temperature.
[0106] S3. Post-processing: After the solder joints have cooled and solidified, flexible insulating adhesive made of PP material is used to coat the positive and negative electrode transfer solder joints respectively. The coating layer has the same flexibility as the battery body, and the transfer position can be bent and twisted arbitrarily with the battery without stress concentration.
[0107] The obtained positive and negative electrode adapters were encapsulated using 20cm long FEP tubing, with 0.5mL of electrolyte injected. After heat sealing, a 20cm long irregularly shaped flexible battery was obtained, with the positive electrode and negative electrode lengths both being 15cm. After standing for 24 hours, formation treatment was performed. Three parallel samples were designed to undergo the following formation process: Sample 1 was charged to 3.5V at a constant current of 0.02C and then stood for 5 minutes; Sample 2 was charged to 0.02C at a constant current of 0.02C and then stood for 5 minutes. Sample 3 was charged with a constant current of 1C to 4.4V, then charged with a constant voltage of 4.4V until the current ≤0.05C, and left to stand for 5 minutes. Sample 4 was discharged with a constant current of 0.2C to 3V and left to stand for 5 minutes. Sample 5 was charged with a constant current of 0.2C to 3.9V, then charged with a constant voltage of 3.9V until the current ≤0.05C, and left to stand for 10 minutes. After formation, the internal resistance was measured in the cabinet, and then the sample was charged with a constant current of 0.3C to 4.4V and discharged with a constant current of 0.5C to 3V in the cabinet for cycling. The electrical performance was tested, and the results are shown in Table 1.
[0108] Table 1. Electrical performance test results of the irregularly shaped flexible battery prepared in Example 1 Example 2 Unlike Example 1, Example 2 had a positive electrode length of 45 cm, a negative electrode length of 45 cm, and an FEP tube length of 50 cm. All other steps and process parameters were the same as in Example 1. A 50 cm long irregularly shaped flexible battery was fabricated. Three parallel samples were named Sample 4, Sample 5, and Sample 6, and were subjected to formation treatment, following the same process as in Example 1. The electrical performance test results are shown in Table 2.
[0109] Table 2. Electrical performance test results of the irregularly shaped flexible battery prepared in Example 2 Comparative Example 1 Compared to Example 2, in Comparative Example 1, the connection method between the positive electrode and the positive electrode tab was manual winding, and the connection method between the negative electrode and the negative electrode tab was also manual winding. All other steps and process parameters were the same as in Example 2. Three parallel samples were named Sample 7, Sample 8, and Sample 9, and were subjected to formation treatment, with the formation treatment process being the same as in Example 2. The electrical performance test results are shown in Table 3.
[0110] Table 3. Electrical performance test results of the irregularly shaped flexible battery prepared in Comparative Example 1 Comparative Example 2 Compared to Example 2, Comparative Example 2 uses nickel tabs of the same diameter for the negative electrode, and the negative electrode connection method is copper-nickel ultrasonic welding. The positive electrode is still aluminum-aluminum ultrasonic welding, and the positive and negative electrodes are welded simultaneously. Other steps and process parameters are the same as in Example 2.
[0111] Test results show that the electrical performance is close to that of Example 2. After 2000 bends, the battery performance in Example 2 is not significantly abnormal, while the comparative example 2 shows tab breakage, decreased mechanical reliability, and abnormal fluctuations in internal resistance.
[0112] Comparative Example 3 Compared to Example 2, in Comparative Example 3, the negative electrode tab uses enameled copper wire, and the negative electrode connection method is copper-copper ultrasonic welding, with simultaneous welding of positive and negative electrodes. Other steps and process parameters are the same as in Example 2.
[0113] Test results showed that none of the 10 batteries could be soldered on, and all the adapters failed.
[0114] Comparative Example 4 Compared to Example 2, in Comparative Example 4, step S3 did not involve wrapping the solder joints with flexible insulating adhesive. Other steps and process parameters were the same as in Example 2.
[0115] Test results showed that the battery short-circuited even without being bent, making it unable to charge or discharge normally.
[0116] As can be seen from the above embodiments and comparative examples, the present invention significantly improves the structural stability, flexible service life and electrochemical performance of irregularly shaped flexible batteries by using the transition method of positive electrode aluminum-aluminum ultrasonic welding and negative electrode copper-copper low-temperature tin welding, combined with pretreatment, step-by-step cooling and flexible insulating glue coating. At the same time, it greatly improves the welding yield and has good industrialization prospects.
[0117] The electrical performance test results show that copper-copper cannot be ultrasonically welded because copper has too high a melting point. Copper-nickel welding is the most common in the lithium battery industry, but nickel wire of the same diameter has high hardness, affecting flexibility. The copper enameled wire used in this invention is the copper wire exposed after the enameled wire is stripped. Through ultrasonic welding of aluminum to aluminum on the positive electrode and low-temperature tin welding of copper to copper on the negative electrode, combined with flexible insulating adhesive coating and post-treatment, it can effectively solve the problems of poor flexibility, many welding defects, unbalanced mechanical properties of positive and negative electrodes and unstable electrical performance in the tab connection of existing irregularly shaped flexible batteries. It achieves balanced mechanical properties of positive and negative electrode connection and meets electrochemical performance standards, thus meeting the mass production and flexible service requirements of irregularly shaped batteries.
[0118] The aforementioned irregularly shaped flexible battery and its positive and negative electrode transfer process employ the same material for the positive electrode tab end and the positive electrode current collector, as well as the negative electrode tab end and the negative electrode current collector. Corresponding welding and low-temperature soldering processes are implemented, effectively avoiding micro-cracks, incomplete welds, and electrochemical corrosion caused by differences in thermal expansion coefficients and electrochemical potential at the interface of dissimilar metals. Simultaneously, the surface treatment and leveling processes in the pretreatment stage significantly improve the surface cleanliness and flatness of the transfer area, resulting in a uniform and dense metallurgical bonding interface at the microscale of the positive and negative electrode transfer solder joints. This achieves a balance in the mechanical properties of the positive and negative electrode transfer, meaning that tensile strength and bending fatigue resistance tend to be consistent. This eliminates localized stress concentration and flexibility failure caused by mismatched welding strength in traditional processes, ensuring the structural integrity and electrical connection reliability of the tab transfer area during repeated bending and service. Furthermore, the stepwise temperature control of the first and second cooling processes effectively suppresses grain coarsening and residual thermal stress in the weld heat-affected zone, significantly reducing the incidence of welding defects. Combined with the post-processing insulation coating of the positive and negative electrode junctions, the electrical insulation safety of the junction area is ensured, while further enhancing the junctions' resistance to environmental corrosion and mechanical protection. The synergistic effect of these processes enables the irregularly shaped flexible battery of this invention to possess excellent flexibility and bending durability while fully meeting all electrochemical performance standards. Moreover, the process is simple, has a wide process window, and a high yield, fully satisfying the needs of large-scale mass production of irregularly shaped batteries and the reliability requirements for long-term flexible service.
[0119] The irregularly shaped flexible battery prepared using the process of this invention exhibits essentially the same pull-out force between the positive and negative electrode transition regions, resulting in excellent structural stability and significantly improved bending fatigue life. The initial coulombic efficiency after battery formation can reach over 90%, and all electrochemical indicators, such as internal resistance, cycle stability, and rate performance, meet industry standards and usage requirements. This process boasts high precision and minimal thermal damage, and is adaptable to the tab connection of micron-level ultrafine fiber batteries, filling a gap in the industry for precise connection technology of ultrafine irregularly shaped flexible batteries. Furthermore, the process route is simple, with strong process compatibility, enabling automated mass production of irregularly shaped batteries in multiple specifications and in large quantities.
[0120] The above technical solutions of the present invention are merely preferred embodiments of the present invention and do not limit the patent scope of the present invention. All equivalent transformations made using the present invention specification under the technical concept of the present invention, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. A process for connecting the positive and negative electrodes of an irregularly shaped flexible battery, characterized in that, Includes the following steps: S1. Pretreatment: The positive current collector transition area, the negative current collector transition area, the positive electrode tab end, and the negative electrode tab end are respectively surface treated and leveled; S2. Positive electrode connection and negative electrode connection: The positive electrode tab end is welded to the positive electrode current collector connection area to form a positive electrode connection solder joint, and then subjected to the first cooling; The negative electrode tab end and the negative electrode current collector transfer area are subjected to low-temperature soldering to form a negative electrode transfer solder joint, followed by a second cooling process. S3. Post-processing: The positive electrode transfer solder joint and the negative electrode transfer solder joint are respectively subjected to insulation coating treatment to obtain an irregularly shaped flexible battery; The positive electrode tab and the positive current collector are made of the same metal material.
2. The positive and negative electrode transfer process for irregularly shaped flexible batteries according to claim 1, characterized in that, The positive current collector is an aluminum wire; The positive electrode tab is made of aluminum wire; The negative electrode current collector is a copper wire; The negative electrode tab is made of copper wire.
3. The positive and negative electrode transfer process for irregularly shaped flexible batteries according to claim 2, characterized in that, The positive electrode tab is made of enameled aluminum wire with a diameter of 0.1~0.2mm; The negative electrode tab is made of enameled copper wire with a diameter of 0.1~0.2mm.
4. The positive and negative electrode transfer process for irregularly shaped flexible batteries according to claim 1, characterized in that, The welding process includes ultrasonic welding; The welding process is performed at a pressure of 0.2~0.6 MPa; The frequency of the welding process is 20~40 kHz; The welding process lasts for 0.15 to 0.5 seconds. The pressure holding time after welding is 0.2~0.6 s.
5. The positive and negative electrode transfer process for irregularly shaped flexible batteries according to claim 1, characterized in that, The welding temperature of the low-temperature soldering is 180~220℃; The welding time for the low-temperature soldering is ≤2s.
6. The positive and negative electrode transfer process for irregularly shaped flexible batteries according to claim 1, characterized in that, The surface treatment of the positive current collector transfer area and the negative current collector transfer area includes micro-grinding, as well as degreasing and / or dust removal, to remove the oxide layer and oil stains from the surface of the transfer area. The duration of the first cooling is 10~40s; The second cooling time is 10~40s.
7. The positive and negative electrode transfer process for irregularly shaped flexible batteries according to claim 1, characterized in that, Both the positive electrode tab and the negative electrode tab are treated with paint stripping. The length of the paint stripping process is 1~2mm; The overlap length between the positive electrode tab end and the positive current collector transfer area is 1~2mm; The overlap length between the negative electrode tab end and the negative electrode current collector transfer area is 1~2mm.
8. The positive and negative electrode transfer process for irregularly shaped flexible batteries according to claim 1, characterized in that, The insulation coating process uses flexible insulating adhesive. The flexible insulating adhesive includes at least one of PP, PE, and lithium battery separator materials.
9. A type of irregularly shaped flexible battery, characterized in that, It is prepared using the positive and negative electrode transfer process of the irregularly shaped flexible battery as described in any one of claims 1 to 8.
10. The irregularly shaped flexible battery according to claim 9, characterized in that, The outer casing of the irregularly shaped flexible battery is made of FEP tubing; The positive current collector and the negative current collector are encapsulated inside the FEP tube; The irregularly shaped flexible battery is in a fiber state; The diameter of the irregularly shaped flexible battery is 1.35~3mm; The protective layer thickness of the irregularly shaped flexible battery is 0.15~1mm.